Value of 17β-oestradiol in prevention of contracture formation - Akeson, Wayne H. (1976)
Akeson, W. H., Woo, S. L-Y., Amiel, D., Doty, D. H., and Rutherford, L. (1976).Annals of the Rheumatic Diseases, 35, 429-436. Value of 17β-oestradiol in prevention of contracture formation. Male and female rabbits were treated with 17β-oestradiol during the 9-week development of a contracture in the left hind limb. The right hind limb served as the paired control. Untreated (absolute control) animals received saline injections. After 9 weeks biochemical analyses of water, hexosamine, soluble and total collagen, as well as biomechanical measurements of joint stiffness, were performed on the dissected knees. In all cases 17β-oestradiol reduced the measured stiffness in the contractures by approximately 50% as compared to the contractures of the untreated animals. 17β-oestradiol, in addition, partially prevented the loss of water and hexosamine which occurs in untreated contractures. 17β-oestradiol administration also decreased the content of soluble collagen fractions in the periarticular connective tissue of both the control and experimental knees. The relationship of these biochemical findings to their mechanical consequences is discussed, and the results are related to a working hypothesis of stress- and motion-dependent homoeostasis within periarticular connective tissue.